Advantages and Disadvantages in Virtual Training / Performances - Apoorva G. Murthy, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
Virtual training and performances became highly popular only during the recent times, starting from 2020. The most popular reason being the Pandemic. Terror rose among the masses due to spread of virus and the whole world came to a still not knowing exactly how to get on with regular routines. Technology is a fast growing domain from the very beginning and is widespread, re- liable, cost effective and time saving. By the time of 2020 almost every household was dependant on internet and their routine was intertwined with it. In the field of Arts, virtual dependence was a less popular facet. Since the pandemic, even the artist's life was dwindling and the struggle to keep them occupied or even look for a job had to be based on the internet. Classes were conducted online through software's and applications. As the creative minds were put into work an idea of virtual performances also came into light, either live or recorded. Although opinions on highs and lows of virtual dependency can be quite sceptical in recent times due to the infectious influence of technology, it always spirals down to in- dividual experience and intrigue on what to choose and what not to.
Keywords: Virtual dependence; Performance; Software; Guru Shishya Parampara; Pandemic; Advantages and Disadvantages